Library planning in Germany - Geisselmann, Friedrich (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
The position and the efficiency of German libraries are rather ambivalent. On the one hand the infrastructure is quite well developed: 2000 public library systems with full time personnel, 275 million books issued, 75 million Euro for acquisitions; 280 scientific general libraries, 60 million books issued, 1300 million Euro for acquisitions. Nevertheless there are a lot of problems, which arise from the administrative structure and the political position of libraries.